Effect of speed and back pressure on the performance of screw press in dewatering of cassava mash - Kolawole, P.; Agbetoye, L.A.S.; Ogunlowo, A.S.; Samuel, T.M. (2012)
A cassava mash process handling machine was developed and tested. Studies were conducted on the effect of screw speed at 20rpm to 100rpm at 20rpm interval. Back pressure was induced by the use of spring of 100N, 200N and 300N. Using a TMS 4(2)1425 variety of cassava, the performance of the screw press unit of the machine was evaluated. The operating parameter of the machine at 40-50 rpm produce a mash with an average moisture content of 52% moisture content wet basis. With the back pressure set at 200N as the machine standard.